In vitro Anti-inflammatory Evaluation of 6-Thioguanine and 6-Hydroxy-2-Mercaptopurine as A Potential Treatment for Rheumatoid Arthritis - Nurul Syuhada Nordin; Yong Yoke Keong; Siti Farah Md Tohid; Zetty Nadia Md Zain; Muhammad Nazrul Hakim (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Eventhough 6-Mercaptopurine act as a major drug for rheumatoid arthritis (RA) treatment, however, its toxicity become a limitation. Therefore, this current study investigated whether 6-hydroxy-2-mercaptopurine (6H2MP) and 6-thioguanine (6TG) compounds are purine nucleoside analogues as a potential treatment of RA. The objective was to evaluate the therapeutics effects, especially the anti-inflammatory potential of 6H2MP and 6TG in the lipopolysaccharides (LPS)-induced RAW264.7 cells and phorbol myristate acetate (PMA)-induced HIG-82 cells.METHODS: Macrophage cells (RAW264.7) and rabbit synoviocytes (HIG-82) cells were induced using LPS and PMA to evaluate the anti-inflammatory potential of 6H2MP and 6TG. The cytotoxicity assessment was done by using MTT assay, while enzyme-linked immunosorbent assay (ELISA) was used to determine the anti‑inflammatory potential, including tumour necrosis factor (TNF-α), interleukins (IL-1β, and IL-6).RESULTS: Upon LPS-induced, RAW 264.7 macrophages demonstrated that 6H2MP and 6TG could suppress the production of nitric oxide (NO) in vitro. The half-maximal inhibitory concentration (IC50) value of 6TG and 6H2MP were 10.73 and 13.31, respectively. Further studied in PMA-induced HIG-82 synovial fibroblast cells showed that 6H2MP and 6TG also suppressed the release of NO, Prostaglandin E2 (PGE2), and inflammatory cytokines such as TNF-α, IL-1β and IL-6. The 6TG is more effective to reduce inflammatory reactions compared to 6H2MP, by the lower dose needed compared to 6H2MP in all experiments except in PGE2.CONCLUSION: The inhibition of inflammatory mediators is an important mechanism by which 6TG and 6H2MP may alleviate pain and articular inflammation. These results indicated that 6H2MP and 6TG are effective candidates for ameliorating inflammatory-associated complications.KEYWORDS: anti-inflammatory, HIG-82 cells, RAW264.7 cells, 6-Thioguanine, 6-Hydroxy-2-Mercaptopurine